Predictors of Renal Dysfunction following Endovascular and Open Repair of Abdominal Aortic Aneurysms - Zettervall, Sara L. (J Vasc Surg, 2016)
OBJECTIVES: Renal complications following repair of abdominal aortic aneurysms (AAA) have been associated with increased morbidity and mortality. However, limited data have assessed risk factors for renal complications in the endovascular era. This study aims to identify predictors of renal complications following endovascular (EVAR) and open repair. METHODS: Patients who underwent EVAR or open repair of a non-ruptured infrarenal AAA between 2011 and 2013 were identified in the Targeted Vascular module of the National Surgical Quality Improvement Project. Patients on hemodialysis preoperatively were excluded. Renal complications were defined as new postoperative dialysis or creatinine increase greater than 2mg/dL. Patient demographics, comorbidities, glomerular filtration rate (GFR), operative details, and outcomes were compared using univariate analysis between those with and without renal complications. Multivariable logistic regression was utilized to identify independent predictors of renal complications. RESULTS: We identified 4503 patients who underwent elective repair of infrarenal AAA (EVAR: 3869, Open: 634). Renal complication occurred in 1% of patients following EVAR and 5% of patients following open repair. There were no differences in comorbidities between patients with and without renal complications. A preoperative GFR < 60 occurred more frequently among patients with renal complications (EVAR: 81% vs. 37%, P < .01; Open: 60% vs. 34%, P < .01). 30-day mortality was also significantly increased (EVAR: 55% vs. 1% P < .01; Open: 30% vs. 4% P < .01). After adjustment, renal complications were strongly associated with 30-day mortality (Odds Ratio (OR): 38.3 95% Confidence Interval (CI): 20.4–71.9). Independent predictors of renal complications included: GFR < 60 (OR: 4.6, 95% CI: 2.4–8.7), open repair (OR: 2.6, 95% CI: 1.3–5.3), transfusion (OR: 6.1, 95% CI: 3.0–12.6), and prolonged operative time (OR: 3.0, 95% CI: 1.6–5.6). CONCLUSION: Predictors of renal complications include elevated baseline GFR, open approach, transfusion, and prolonged operative time. Given the dramatic increase in mortality associated with renal complications, care should be taken to employ renal protective strategies, achieve meticulous hemostasis to limit transfusions, and to utilize an endovascular approach when technically feasible.